Penatalaksanaan Hipertensi di Era Pandemi COVID-19 - Irma Kartikasari; Muhammad Afif (PROCEEDING UMSURABAYA, 2023)
AbstractHypertension is the leading risk factor for adverse cardiovascular disease outcomes. Coronavirus disease 2019 (COVID-19) has become a worldwide pandemic responsible for millions of deaths around the world. Hypertension has been identified as one of the most common comorbidities and risk factors for severity and adverse outcome in these patients. Concern has been expressed that treatment with ACEIs or ARBs might increase the risk of infection, or developing the severe consequences of infection with COVID-19. Numerous original studies and meta-analysis reported no relationship with severity or mortality in COVID-19 patients or even benefit of taking renin-angiotensin-aldosterone inhibitors in COVID-19 patients. The goal of the various hypertension guidelines is to provide easily accessible information to healthcare providers and public health officials, which is key for optimal clinical practice. However, the COVID-19 pandemic has challenged the ability to provide safe care to the most vulnerable hypertensive populations throughout the world. The aim of this review article is to provide an overview of the current evidence on hypertension management in Covid-19 pandemic era. Keywords: Hypertension, COVID-19, Anti-Hypertensive Drugs, Cardiovascular DiseaseAbstrak